Clinical features and factors associated with short-term prognosis in patients with pulmonary embolism - V.Y. Tseluyko; L.M. Yakovleva; S.M. Sukhova; O.V. Radchenko; T.V. Pylova; A.S. Vnukova; K.Yu. Kinoshenko (Кардіохірургія та інтервенційна кардіологія)
The aim – to study the clinical, anamnestic and instrumental parameters associated with short-term prognosis in patients with pulmonary embolism (PE).